Simulation of atomization and ignition of high-pressure jet stream - Bolegenova, S.; Askarova, A.; Ospanova, Sh.; Pilipenko, N.; Shortanbayeva, Zh.; Aldiyarova, A. (Recent Contributions to Physics, 2023)
This work is a significant study in terms of modern combustion physics of the problem of computer modeling of atomization, ignition, and combustion of high-pressure reactive liquid fuels under high turbulence. The need for a detailed study of the physical and chemical processes occurring during the combustion of reactive fuels is determined by the increased requirements for the efficiency of various technical devices, the accuracy of ignition prediction, and the combustion rate conditioned by the current environmental requirements for environmental protection. The processes of atomization, ignition, and combustion of atomized jet fuel (heptane) at high pressures were investigated using a numerical model. Numerical simulation methods were used to get profiles of the temperature plume, distribution of concentrations of the oxidizer, and reaction products (carbon dioxide and soot) in the combustion space. The optimum value of the initial pressure for heptane has been determined. The practical significance of the computational experiments presented in this paper is that the results obtained can be used in designing various reactive technical devices using combustion, which would simultaneously solve the problem of optimizing the process, increasing fuel combustion efficiency, and minimizing emissions of harmful substances.